Refined estimates of the decoder complexity in the model of cellular circuits with functional and switching elements - S.A. Lozhkin; V.S. Zizov (Учёные записки Казанского университета: Серия Физико-математические науки)
The model of cellular circuits was considered in a single basis of functional and switching elements, which is built in accordance with the standard basis B0 consisting of Boolean functions x1 & x2, x1 ∨ x2, ˉx1. In this model, both inputs and outputs of the cellular circuit Σ associated with various input and output Boolean variables, respectively, are irreversibly located on the border of the corresponding rectangular lattice, and the cellular circuit Σ itself corresponds, structurally and functionally, to a scheme of functional elements S in the basis B0 with the same sets of input and output Boolean variables.